Readers’ Letters and Editorial Polemics in the Jadid Press of Early Twentieth‑Century Turkestan - Satibaldieva, Nigora Alimqul qizi; Medd , Graeme (The Lingua Spectrum, 2026)
This article examines readers’ letters and editorial polemics as mechanisms through which Jadid ideas circulated in the printed press of twentieth‑century Turkestan. It shows how letter columns, local correspondences and editorial replies turned newspapers and journals into a venue for public discussion on the “new method” school, language reform, social ethics and cultural modernization. The paper combines historical‑discursive analysis with a genre perspective and applies the public‑sphere framework to a colonial setting. The study draws on a corpus of Jadid and enlightenment periodicals (including Taraqqiy, Sadoi Turkiston and Oyina) and on key scholarship about Central Asian print culture and Muslim cultural reform. Findings indicate that readers’ letters served as “social diagnostics” and supported reform legitimacy, while editorial polemics translated everyday grievances into programmatic arguments and responsibility. Interactive features of print – feedback, replies and thematic series – thus strengthened diffusion by widening audiences and stabilizing norms of public discussion.